UPAYA MENINGKATKAN HASIL BELAJAR IPS MELALUI MODEL PEMBELAJARAN MAKE A MATCH PADA SISWA KELAS IX SMP NEGERI 2 NANGA PINOH - Rika Sri Aprilla Krisanti (STKIP Persada Khatulistiwa Sintang, 2022)
The study aims to whether there is an effect of learning models make a match on Social Studies learning outcomes of ninth grade students of SMPN 2 Nanga Pinoh. The method used in this study is classroom action research (CAR) which consist of two cylcles. Each round consist of four stages; planning, observing, reflecting, and revising. The location of the study was at SMP Negeri 2 Nanga Pinoh. The research subjects were students of class IX in academic year 2021/2022. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results analysis, it was found that student achievement increase from cycle 1 to cycle II. Cycle 1 (65,38%), cycle II (88,46%). The conclusion of this study is the make a match method can positively influence the achievement and motivation of students in class IX SMPN 2 Nanga Pinoh I academic year 2021/2022 and this learning model can be used as an alternative to Social Studies learning.